Pengaruh Lingkungan Kerja terhadap Kinerja Pegawai pada Kantor Camat Muara Sabak Tanjung Jabung Timur - Murniyati Murniyati (Science of Management and Students Research Journal (SMS), 2019)
The purpose of this study is to describe the work environment and employee performance at the Muara Sabak Sub-District Head Office, Tanjung Jabung Timur.To analyze the influence of the work environment on employee performance at the Muara Sabak Sub-District Head Office, Tanjung Jabung Timur.In conducting organization or company activities, the work environment is all the conditions that are located around the workers, so that either directly or indidirectly can affect him in carrying out the tasks charged Methods of data collction in this study using damage research and field research by collectinf data usinf questionnaire techniqus or collect data by preparing a list of statements. And information soureed from the internet for theory retrieval.Subdistrict Muara Sabak Tanjung Jabung Timur is area formed under the law Constitution Number .54 year 1999 Subdistrict Muara Sabak Tanjung Jabung Timur.Based on the results of the regression analysis abowed that the regression equation Y = 1,413 + 0,930X with R² 0.834. Partially, the work environment affect on the performance of employees at Kantor Muara Sabak Tanjung Jabung Timur, with value of 4.320 and significant levels 0.000.In this study, outhors give suggestion that is should Kantor Camat Muara Sabak Tanjung Jabung Timur more intensively pay attention to work environment will affect even better, with continue to improve comfort and security.Keyword: Work Environment, Employee Performance